2015
DOI: 10.1039/c5ra01123j
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of spinel ferrite based alkaline anion exchange membrane water electrolysers for hydrogen production

Abstract: Alkaline anion exchange membrane water electrolysis (AEMWE) is considered to be an alternative to proton exchange membrane water electrolysis (PEMWE), owing to the use of non-noble meta/metal oxides in AEMWE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 58 publications
(69 reference statements)
0
41
1
Order By: Relevance
“…It must be considered that for implementation into a commercial system, ideally catalysts should be grown on the electrodes themselves such as Ni foam or stainless steel, however these results indicate that natural materials show interesting properties and indeed face the same challenge of stable adherence to electrodes as their synthetically prepared counterparts. Perhaps fabricating membrane electrode assemblies for utilisation in the next generation of anion exchange membrane electrolysers is the most appropriate way forward for this type of material. To understand the origin of the activity of this material a detailed structural and chemical analysis was undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…It must be considered that for implementation into a commercial system, ideally catalysts should be grown on the electrodes themselves such as Ni foam or stainless steel, however these results indicate that natural materials show interesting properties and indeed face the same challenge of stable adherence to electrodes as their synthetically prepared counterparts. Perhaps fabricating membrane electrode assemblies for utilisation in the next generation of anion exchange membrane electrolysers is the most appropriate way forward for this type of material. To understand the origin of the activity of this material a detailed structural and chemical analysis was undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…This observation stresses the importance of the role of the anionselective polymer binder when deionized water (or highly diluted alkaline solutions) is utilized as the circulating medium. It can be Transactions of the ASME further documented by the example of the Fumatech membrane, where the data are available [96,97]. Utilizing a non-PGM catalyst and an anion-selective polymer binder, it was possible to achieve significantly higher current density (0.25 A cm −2 @ 1.8 V) [97] when compared to a cell based on PGM catalyst with inert PTFE binder (0.02 A cm −2 @ 1.8 V) [96].…”
Section: Performance Of Commercial Membranes In Anionmentioning
confidence: 99%
“…It has been reported that, the peaks centered at BE 639.7 eV, 640.9 eV, 651.2 eV and 652.3 eV are assigned to Mn 2+ ions, and the satellite feature centered at BE 646.4 eV is also a typical feature for Mn 2+ ions. [40][41][42] Binding energy difference (DBE) in Mn 3s region of XPS spectrum is another important parameter to distinguish chemical state of Mn element, and DBEs of 6.0 eV, 5.3 eV and 4.7 eV correspond to Mn 2+ , Mn 3+ , and Mn 4+ ions, respectively. 43 DBEs of Mn 3s regions for all the oxide scales are 6.0 eV (Fig.…”
Section: Chemical State Of Elements On the Oxide Scalesmentioning
confidence: 99%